T-cell activation and senescence in asymptomatic HIV/Leishmania infantum co-infection. - Carolina de Oliveira Mendes-Aguiar; Manoella do Monte Alves; Amanda de Albuquerque Lopes Machado; Glória Regina de Góis Monteiro; Iara Marques Medeiros; Jose Wilton Queiroz; Iraci Duarte Lima; Eliardo G Costa; Richard D Pearson; Mary E Wilson; Marshall J Glesby; Eliana Lúcia Tomaz do Nascimento; et al. (PLoS Neglected Tropical Diseases)
Background Leishmania infantum can be an opportunistic pathogen, with an immunocompromised status increasing the risk of converting asymptomatic infection to symptomatic visceral leishmaniasis (VL). VL has approximately 5% fatality rate; and HIV coinfection (AIDS/VL) increases this risk. We hypothesized that, relative to those with HIV alone, people with co-infection would have altered T cell activation which could impact on the risk of VL. Methods A cross-sectional study was performed between 2014 and 2016 to determine the prevalence of L. infantum infection in people living with HIV (PLHIV) residing in Brazil (n = 1,372). Subsequent incident cases of VL were ascertained from a public health database through 2018 and from a cohort of families with VL. Immune status of 69 participants was evaluated and comparisons made between those with and without HIV, with latent or with active Leishmania infection and those without HIV but with active or resolved Leishmania or T cell hypersensitivity to Leishmania antigen and healthy control subjects. Results A total of 24.2% of PLHIV had positive anti-IgG L. infantum antibodies. The relative risk of developing AIDS/VL was 2.27 (95% CI: 0.920 to 5.59; p = 0.07) to HIV/Leish coinfected subjects with positive leishmania serology compared to HIV subjects without leishmania serology. Poor adherence to antiretroviral therapy (p = 0.0008) or prior opportunistic infections (p = 0.0007) was associated with development of AIDS/VL in asymptomatic HIV/Leish. CD4+ and CD8+ T cells counts or viral load were similar between asymptomatic HIV/Leish and HIV subjects. However, activated CD8+CD38+HLA-DR+ T cells were higher in asymptomatic HIV/Leish than HIV. Likewise, senescent (CD57+) and PD1+ CD8+ T cells were higher in asymptomatic HIV/Leish than in AIDS/VL or HIV groups. Conclusion Although asymptomatic HIV/Leish subjects had CD4+ and CD8+ T cells similar to HIV alone, their CD8+T cells had increased activation and senescence which could contribute to risk of developing VL.